Phytochemical profile and anti-lipoxygenase activity of alcoholic extracts of plant species from asteraceae family - Torres Carro, Romina (2012)
Usage of medicinal plants with curative purpose is an ancient and common practice still in use now a day. On physiopathology of sicknesses that develop an inflammatory and allergic process, lipoxygenase (LOX) has an important role being the enzymes responsible of the biosynthesis of inflammatory mediators. We evaluated the anti-LOX capacity of alcoholic extracts of nine plant species (B. boliviensis, B. incarum, Ch. keidelii, C. atacamensis, N. armatum, P. lepidophylla, P. lucida, P. phyliciformis, T. absinthioides) belonging to Asteraceae family and its relation to its phytochemical profile. Tinctures of plants collected in Argentine Puna were analyzed. Total polyphenols content vary between 64-160 µg Gallic Acid Equivalents, GAE/mg, phenolics non flavonoids vary between 53- 153 µg GAE/mg, flavones/flavonols between 6- 28 µg Quercetin Equivalents/mg and flavonones/dihidroflavonones between 24 and 51 µg Naringenin Equivalents/mg. Species from genus Parastrephia presented the highest inhibitory activity over LOX with IC50 values between 219 and 253 µg/ml, being P. lepidophylla the most active one. This could be related to the higher levels of total phenolics and flavones/flavonols measured in this species. The results indicate the potential use of Parastrephia extracts as natural anti-inflammatory.